Association between malnutrition and contrast-associated acute kidney injury in congestive heart failure patients following coronary angiography - Ying, Ming; Yang, Junqing; Huang, Zhidong; Ling, Yihang; Wang, Bo; Huang, Haozhang; Li, Qiang; Liu, Jin; Liu, Yong; Chen, Zhujun (Frontiers in Nutrition, 2022)
Background Previous studies have shown that malnutrition is very common in patients with congestive heart failure (CHF) and is closely related to the occurrence of acute kidney injury. However, the relationship between malnutrition and contrast-associated acute kidney injury (CA-AKI) is unclear. Method and results We obtained data from 842 patients who were diagnosed with CHF following coronary angiography (CAG) or percutaneous coronary angiography (PCI) and had follow-up information from January 2013 to February 2016. The patients were divided into 3 groups according to the Controlling Nutritional Status Score before CAG or PCI procedure (Group 1: Normal; Group 2: Mild Malnutrition; Group 3: Moderate to Severe Malnutrition). The main endpoint was CA-AKI. Univariate and multivariable logistic regression analyses were performed. 556 (60.0%) patients suffered from malnutrition before CAG or PCI. During a median follow-up of 2.1 years, A total of 49 (5.82%) patients developed CA-AKI. Additionally, 5 (1.75%), 26 (6.27%) and 18 (12.77%) events were documented in patients with normal, mild and moderate or severe malnutrition, respectively (p < 0.01). In multivariable-adjusted models, patients with malnutrition showed a significantly higher incidence of CA-AKI than those in the normal group. Conclusion Malnutrition is an independent risk factor for CA-AKI in CHF patients following CAG.